بناء وتطبيق مقياس القلق الاحصائي لدى طلبة قسم العلوم التربوية والنفسية - راضي عبود جواد (Journal of College of Education, 2018)
The present research aims at designing and applying a scale in the statistical anxiety for the students at educational and psychological sciences. It is applied on a sample of (100) male and female students in the second and third year; namely ; (37) male and female students from the second year, and (63)from the third year .The final form of the tool is composed of (30) items .The face validity and the construct validity are secured as well as the reliability by using test and retest formula and Cronbach’s Alpha .The result obtained show that there is a statistical significant difference in the trait of the statistical anxiety .The result also revealed that there is a statistical significant difference according to the sex variable in favor of the male students and according to the grade variable in favor of the third year students .